A Concordance study of CT densitometry with DXA densitometry - Ruwani Mawella; R Rajak (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2022)
Osteoporosis is a skeletal disorder characterized by compromised bone strength resulting in an increased risk of fracture [1]. Bone Mineral Density (BMD) is responsible for 60-90% of the strength of bone [1] and the current standard of assessment is by Dual-energy X-Ray Absorptiometry (DXA). DXA generates T-scores of the lumbar spine, femoral neck, or hip by calculating the difference between the individual's BMD and the population mean, divided by the standard deviation of the reference population. The World Health Organisation (WHO) classifies osteoporosis at a T-score of or below -2.5.